Health-related quality of life among patients with treated alcohol use disorders, schizophreniform disorders or affective disorders and the influence of flexible and integrative psychiatric care models in Germany (PsychCare) - Neumann, Anne; Soltmann, Bettina; Kliemt, Roman; Weinhold, Ines; Schmitt, Jochen; Pfennig, Andrea; Baum, Fabian (Frontiers in Psychiatry, 2023)
Introduction: Flexible and integrated treatment options (FIT) have been established in German psychiatric hospitals to enhance continuous and patient-centered treatment for patients with mental disorders. We hypothesized that patients with experience in FIT treatment showed higher health-related quality of life (HRQoL) and comparable symptom severity compared with patients treated as usual (TAU). Further, we expected that some sub-dimensions of HRQoL determined HRQoL results clearer than others, while certain factors influenced HRQoL and symptom severity stronger in the FIT compared to the TAU group. In addition, we hypothesized that HRQoL is correlated with symptom severity. Methods: We undertook a controlled, prospective, multicenter cohort study (PsychCare) conducted in 18 psychiatric hospitals in Germany, using the questionnaires Quality of Well Being Self-Administered (QWB-SA) (HRQoL) and Symptom-Checklist-K-9 (SCL-K-9) (symptom severity) at recruitment (measurement I) and 15 months later (measurement II). We assessed overall HRQoL (measured in health utility weights (HUW)) and symptom severity score for patients from FIT and TAU treatment. We investigated the QWB-SA dimensions and separated the results by diagnosis. We used beta regressions to estimate the effect of multiple co-variates on both outcomes. To investigate the correlation between HRQoL and symptom severity, we used Pearson correlation. Results: During measurement I, 1,150 patients were recruited; while 359 patients participated during measurement II. FIT patients reported higher HUWs at measurement I compared to TAU patients (0.530 vs. 0.481, p=0.003) and comparable HUWs at measurement II (0.581 vs. 0.586, p=0.584). Symptom severity was comparable between both groups (I: 21.4 vs. 21.1, p=0.936; II: 18.8 vs. 19.8, p=0.122). We found lowest HRQoL and highest symptom severity in participants with affective disorders. HRQoL increased and symptom severity decreased over time in both groups. The QWB-SA dimension acute and chronic symptoms was associated with highest detriments in HRQoL. We identified risk / protective factors that were associated with lower quality of life and higher symptom severity in both groups. We confirmed that HRQoL was negatively associated with symptom severity. Discussion: HRQoL (during hospital treatment) was higher among patients treated in FIT hospitals compared to patients in routine care, while symptom severity was comparable between both groups.